ผลของกลุ่มการปรึกษาเชิงจิตวิทยาแนวซาเทียร์ต่อความสอดคล้องกลมกลืนในตนของนิสิตนักศึกษามหาวิทยาลัย - ไพลิน ลิ้มวัฒนชัย (จุฬาลงกรณ์มหาวิทยาลัย, 2013)
The purpose of this study was to examine the effect of Satir group counseling on congruence of undergraduate students through quasi-experimental with pretest-posttest control group design. Thirty-two undergraduate students were assigned to 2 experimental groups of 8 and 2 control groups of 8 people, conducted by researcher. There were 9 sessions over a period of 24 hours in total, during 3 weeks. The control groups were not given any treatment during the experiment period. The Instrument was Congruence Scale. A two-way repeated measures ANOVA statistics was used for data analysis. Findings revealed: 1.The posttest scores on congruence of the experimental group are higher than its pretest scores at the .001 level of significance.2.The posttest scores on congruence of the experimental group are higher than the posttest scores of the control group at the .001 level of significance.3.The follow–up scores (3 weeks post - program) on congruence of the experimental group does not yield significant difference when compared to the posttest scores at the .05 level of significance.